Monitoring of Cytomegalovirus Infection in Solid-Organ Transplant Recipients by an Ultrasensitive Plasma PCR Assay - Hadaya, Karine (American Society for Microbiology, 2003)
Early and accurate monitoring of cytomegalovirus (CMV) infection in solid-organ transplant recipients is of major importance. We have assessed the potential benefit of an ultrasensitive plasma-based PCR assay for renal transplant recipients. The pp65 CMV antigen (pp65 Ag) assay using leukocytes was employed as a routine test for the monitoring of CMV in 23 transplant recipients. We compared the pp65 antigenemia with the CMV load quantified by an ultrasensitive PCR (US-PCR) with a limit of detection of 20 CMV DNA copies/ml of plasma. CMV infection was detected in 215 (67%) of 321 plasma samples by the US-PCR compared with 124 (39%) of 321 samples by the pp65 Ag assay. The US-PCR assay permitted the detection of CMV infection episodes following transplantation a median of 12 days earlier than the pp65 Ag assay. Moreover, during CMV infection episodes, DNA detection by the US-PCR was consistently positive, whereas false negative results were frequently observed with the pp65 Ag assay. We found a good correlation between the two assays, and the peak viral loads were significantly higher in patients with CMV-related complications (median, 5,000 DNA copies/ml) than in those without symptoms (1,160 DNA copies/ml) (P = 0.048). In addition, patients that did not require preemptive therapy based on the results of the pp65 assay had CMV loads significantly lower (median, 36 DNA copies/ml) than those that needed treatment (median, 4,703 DNA copies/ml) (P < 0.001). These observations provided cutoff levels that could be applied in clinical practice. The ultrasensitive plasma-based PCR detected CMV infection episodes earlier and provided more consistent results than the pp65 Ag assay. This test could improve the monitoring of CMV infection or reactivation in renal transplant recipients.